PARENTING TRAINING TO BUILD CHILDREN'S CHARACTER THROUGH WEB LEARNING - Wartiningsih Wartiningsih; Sugeng Bayu Wahyono (English Language and Literature International Conference (ELLiC) Proceedings, 2019)
Character building can be done early in the family. Parents need a special formula in educating children's character in an era of disorder. In the digital age, parents can attend childcare training or courses through web learning. This training is to overcome the limitations of place, time, and costs for parents. The purpose of this paper is to explain as an alternative to building the character of children from families through web learning. The method in this paper uses in-depth literature studies. The results of this study that character development can be started from the family as the first pillar of education. Parents can get knowledge about children's character through web learning.